Pengembangan E-Modul Berbasis STEM EDP Untuk Meningkatkan Keterampilan Proses Sains Siswa SD - Maulida, Salwa; Sutisnawati, Astri; Uswatun, Din Azwar (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to development of a STEM-based e-module employing the Engineering Design Process (EDP) approach, specifically designed to enhance elementary students’ science process skills on ecosystem topics. This study develops an interactive digital e-module with EDP steps as the core of science learning activities. The research adopts a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), involving 40 fifth-grade students at SDN Dayeuhluhur CBM and expert validators (content, media, and practitioners). Research instruments include validation questionnaires, pre-test and post-test items, and interview guidelines. Data were analyzed using descriptive quantitative methods and N-Gain analysis. Validation results indicate the e-module is highly feasible for classroom use (average feasibility score: 91%), while the effectiveness test shows a significant increase in science process skills with an N-Gain of 0.72 (high category). Theoretically, these findings reinforce the relevance of integrating STEM-EDP in elementary science education; practically, the developed e-module supports the implementation of the Merdeka Curriculum and strengthens 21st-century competencies through contextual, collaborative, and engaging learning experiences.